Recensioner - Glahn, Henrik (Danish Yearbook of Musicology, 1968)
Review of: Finn Mathiassen: The Style of the Early Motet. An Investigation of the Old Corpus of the Montpellier Manuscript. Studier og publikationer fra Musikvidenskabeligt Institut, Aarhus Universitet, 1. Copenhagen 1966.